Identity and Cultural Recognition in the Curriculum: A Rationale - Ahmed, Khawlah (k@ta: A Biannual Publication on the Study of Language and Literature, 2010)
Culture has become an important component that is addressed in a variety of contexts from the teaching of a language (Baker, 2003), educational equality (Gay, 1997; 2000), to politics and cultural identities (Llosa, 2008; Muller, 2008; Goshgarian, 1998). Empirical and theoretical research shows that students perform better and are more academically and socially successful when their culture is recognized, portrayed favorably in the school curriculum, and used as a fundamental source of information (Nieto, 1996; Diamond and Moore, 1995; Au, 1993; Geyhle, 1983). This paper examines the importance of inclusion and recognition of cultures in school curriculums and presents research that suggests that despite the importance given to this issue in political and social discourse, inclusion of cultures in many curriculums has yet to be fully realized.